Stock Valuation Analysis : P/GMV Dan LTV/CAC Pada Perusahaan Startup Di Asia Dan America - Wendyka Mazaka; Sri Wahjuni Latifah (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
This study aims to evaluate and analyze the fair value of shares of startup companies in Asia and America using the Price to Gross Merchandise Value (P/GMV) and Lifetime Value to Customer Acquisition Cost (LTV/CAC) methods. The company is PT. Bukalapak.com Tbk, SEA Ltd, Ebay Inc, and Shopify Inc. This type of research is descriptive quantitative. The data used is financial report data for the period 218-2020, sourced from the official idx website. Research is conducted by identifying data, calculating formulas, analyzing data, and concluding. The results showed that the company's shares PT.Bukalapak.com Tbk & Ebay Inc. were undervalued, and SEA Ltd. and Shopify Inc. were overvalued. Asian startup stocks are no better than America. The limitation of this research is that there needs to be more data on startup companies listed on the IDX. Future research can expand research with empirical methods.